Community Education on the Appropriate and Safe Use of Over-the-Counter and Pharmacy-Only Medicines - Juwita, Dian Ayu; Rachmaini, Fitri; Rahmah, Rahmah; Sabarita, Najah (Warta Pengabdian Andalas, 2025)
The use of over-the-counter (OTC) and pharmacy-only medicines has significantly increased due to their easy accessibility and the growing trend of self-medication. However, improper use of these medicines can lead to adverse effects, drug interactions, and even resistance. This community service activity aimed to raise public awareness about the rational and safe use of medicines, particularly OTC and pharmacy-only medicines. The activity was conducted using participatory education methods, including the delivery of material on drug classifications, simulation of reading drug labels and understanding usage instructions, as well as interactive sessions such as Q&A and consultations with pharmacists. The evaluation was carried out using pre-test and post-test assessments to measure participants’ knowledge before and after the educational session. The results showed a significant improvement in participants’ knowledge regarding the identification of drug types, label reading, and proper usage instructions. Additionally, participants demonstrated increased awareness of the risks associated with improper medication use and the importance of consulting pharmacists before taking OTC or pharmacy-only medicines. This activity highlights the essential role of pharmacists in public health education and emphasizes the need for structured, interactive educational strategies to promote responsible self-medication practices. Collaboration between healthcare professionals and the community is key to ensuring the safe and appropriate use of non-prescription medicines